Implementasi Praktik Kerja Lapangan di Dinas Pendidikan Kabupaten Gowa: Penguatan Keterampilan Mahasiswa dalam Tata Kelola Pendidikan - Maya Sari Wahyuni; Rahmat Syam; Sahid; Dian Firmayasari; Nur Ahniyanti Rasyid (Jurnal Abdi Bangsa, 2025)
Field Work Practice (PKL) at the Education Office of Gowa Regency for two months (June 10 - August 9, 2024) aims to provide students with real work experience and develop practical skills. The author was involved in operational and administrative activities such as verifying teacher allowance documents, compiling educator data, and serving as a committee member in educational quality improvement programs. A supportive work environment, friendly staff, and adequate facilities facilitated the smooth implementation of the PKL. No significant obstacles were encountered, with the author maintaining discipline and focus. The results show that the PKL offers valuable practical experience for students and makes a positive contribution to the institution and community, while preparing students to face the workforce and supporting the improvement of local education quality.